A COMPREHENSIVE STUDY TO INVESTIGATE THE IMMUNE RESPONSE OF VACCINATION IN CHILDREN AND YOUNG PEOPLE DIAGNOSED WITH INFLAMMATORY BOWEL DISEASE - M. Hadi (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Objectives: The objective of this study was to evaluate the immune response to vaccination in children and young individuals diagnosed with inflammatory bowel disease (IBD). The vaccine response may be influenced by both the underlying disease and its treatment in patients with IBDs. Methods: The review compares the immune response of IBD patients to healthy controls and explores differences between those receiving immunosuppressive therapy (IS) and non-immunosuppressive therapy (NIS). The review aims to assess immune response adequacy, adverse events, and IBD exacerbations. Results: Patients with IBD exhibited diverse immune responses, with influenza B showing the lowest response rate. Immunosuppressive therapy (IS) did not significantly affect response rates compared to non-IS treatment. Lower vaccine responses were associated with IS therapy, steroid use, and certain medications. In general, there were no significant differences in immune response between IBD patients and healthy individuals, except for lower responses to influenza B and hepatitis B vaccines. Adverse events following vaccination were well tolerated, with similar rates in IBD patients and healthy controls. Vaccination had limited impact on disease activity, with only a few isolated cases of IBD exacerbation reported. Conclusions: The immunogenicity of vaccinations in children and young individuals with inflammatory bowel disease (IBD) is comparable to that of healthy individuals, and there is no significant difference in immune response between patients with IBD receiving immunosuppressive (IS) therapy and those without it. However, more research is required to thoroughly investigate this topic, as there are limited well-designed studies available.